2014
DOI: 10.5152/tjbh.2014.1907
|View full text |Cite
|
Sign up to set email alerts
|

Management of Patients with Idiopathic Granulomatous Mastitis: Presentation of 13 Cases

Abstract: Objective: Idiopathic granulomatous mastitis is a rare benign chronic disease of the breast. In this study, we aimed to present our treatment experience in cases diagnosed with idiopathic granulomatous mastitis. Materials and Methods:13 treated cases of idiopathic granulomatous mastitis, diagnosed as a result of histopathological examination, were investi-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…33 studies (55.9%) mentioned ethical approval sought to perform the study: Ahmed, 2016; Alper, 2020; Altunkeser, 2019; Berkesoglu, 2021; Bouton, 2015; Cetin, 2019; Cetinkaya, 2020; Chen, 2021; Chirappapha, 2018; Cornejo-Juarez, 2014; Dalbasi, 2021; Davis, 2019; Erturk, 2021; Farouk, 2017; Fayed, 2019; Joseph, 2014; Kafadar, 2021; Karanlik, 2014; Kiyak, 2014; Maher, 2021; Oak, 2021; Pandey, 2014; Postolova, 2020; Sakurai, 2011; Shin, 2017; Shojaee, 2021; Tan, 2019; Tekgoz, 2020; Toktas, 2021; Wang, 2020; Yabanoglu, 2015; Zhang, 2019; Zhang Xiaohui, 2020. The Çaliş, et al, 2014 and Deng, et al, 2017 studies described no ethical approvals sought, but patients included in the studies had provided written consent ( 40 , 77 ). The remaining 24 studies (40.7%) did not mention any ethical approval: Akahane, 2013; Akcan, 2014; Aldaqal, 2004; Alrayes, 2019; Altintoprak, 2015; Atak, 2015; Atalay, 2011; Dag, 2021; Elzahaby, 2016; Erhan, 2000; Eser, 2013; Gunduz, 2014; Gurleyik, 2012; Hur, 2013; Kayahan, 2012; Kundaktepe, 2021; Lai, 2005; Liao, 2020; Mawla, 2020; Neel, 2013; Ocal, 2010; Sen Oran, 2013; Skandarajah, 2015; Wang, 2021.…”
Section: Resultsmentioning
confidence: 99%
“…33 studies (55.9%) mentioned ethical approval sought to perform the study: Ahmed, 2016; Alper, 2020; Altunkeser, 2019; Berkesoglu, 2021; Bouton, 2015; Cetin, 2019; Cetinkaya, 2020; Chen, 2021; Chirappapha, 2018; Cornejo-Juarez, 2014; Dalbasi, 2021; Davis, 2019; Erturk, 2021; Farouk, 2017; Fayed, 2019; Joseph, 2014; Kafadar, 2021; Karanlik, 2014; Kiyak, 2014; Maher, 2021; Oak, 2021; Pandey, 2014; Postolova, 2020; Sakurai, 2011; Shin, 2017; Shojaee, 2021; Tan, 2019; Tekgoz, 2020; Toktas, 2021; Wang, 2020; Yabanoglu, 2015; Zhang, 2019; Zhang Xiaohui, 2020. The Çaliş, et al, 2014 and Deng, et al, 2017 studies described no ethical approvals sought, but patients included in the studies had provided written consent ( 40 , 77 ). The remaining 24 studies (40.7%) did not mention any ethical approval: Akahane, 2013; Akcan, 2014; Aldaqal, 2004; Alrayes, 2019; Altintoprak, 2015; Atak, 2015; Atalay, 2011; Dag, 2021; Elzahaby, 2016; Erhan, 2000; Eser, 2013; Gunduz, 2014; Gurleyik, 2012; Hur, 2013; Kayahan, 2012; Kundaktepe, 2021; Lai, 2005; Liao, 2020; Mawla, 2020; Neel, 2013; Ocal, 2010; Sen Oran, 2013; Skandarajah, 2015; Wang, 2021.…”
Section: Resultsmentioning
confidence: 99%
“…The first nonsurgical treatment to be used can involve steroid therapy, mostly in patients with severe symptoms. Various immunosuppression treatments or surgical treatments may be recommended in patients with more severe symptoms or highly recurrent IGM [10,11]. Antibiotherapy is not recommended if there is no growth in the patient's culture [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…GM is classified as mild when there are a few localized granulomas and severe when there is extensive involvement, leading to significant inflammation, tissue damage, and more pronounced symptoms, including severe breast pain, swelling, skin changes, nipple retraction, and the formation of draining sinuses or abscesses [ 17 , 18 ]. In light of this, studies have reported on various treatments, including topical and oral medications, injections, and surgical interventions.…”
Section: Methodsmentioning
confidence: 99%